Examining The "Spill-Over" Effect Of Religiosity On Civic Involvement And Efficacy - Smith, H. Lovell (Research in the social scientific study of religion, 2008)
This study examines the hypothesis that religiosity increases civic involvement and efficacy, and especially whether this influence extends beyond involvement in one’s own religious organization. Because of the way that religiosity and civic involvement/efficacy are entwined with race and gender, we consider the confluence of all these factors. Data are derived from the 1655 black or white adults who participated in the 1987 General Social Survey. The outcomes are involvement in faith-based and secular organizations, and political electoral participation, as well as perceived social and political efficacy. In addition to race and gender, potential correlates include cognitive and behavioral indicators of religiosity. Preliminary analysis used chi-square and ANOVA for group comparisons and multivariate analysis of outcomes used logistic regression. Results provide partial support for the hypotheses that faith-based organization involvement is higher among blacks and women and secular involvement/efficacy is higher among whites and men. Religiosity is strongly related to faith-based involvement, but not as strongly nor consistently associated with other forms of civic action and efficacy. Secular involvement is more strongly related than faith-based involvement to perceived social and political efficacy. Findings suggest that religiosity has a small "spill-over" effect, that religious behavior has a greater effect than religious beliefs, and that the effect on perceived social efficacy is greater than that on perceived political efficacy. It remains to be seen whether recent efforts to politicize religious activity have increased the "spill-over" effect.